2017
DOI: 10.1016/j.jvs.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of native superficial femoral artery chronic total occlusion recanalization after failed femoropopliteal bypass

Abstract: In a high-risk cohort when thrombolysis is excluded, BP is superior to EV after failure of a femoropopliteal bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Hence, the idea to recanalize the native SFA chronic total occlusions has been born in patients with critical limb ischemia (CLI) and femoro-popliteal bypass failure, limited to those cases unfit for surgery or refusing surgical reconstruction. Data regarding this approach in femoro-popliteal bypass failure are limited to few case-series studies (Li et al 2018 ; Gandini et al 2009 ; Davies et al 2017 ), so the need for new studies should be emphasized to better understand long-term outcomes of this option compared to secondary bypass surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the idea to recanalize the native SFA chronic total occlusions has been born in patients with critical limb ischemia (CLI) and femoro-popliteal bypass failure, limited to those cases unfit for surgery or refusing surgical reconstruction. Data regarding this approach in femoro-popliteal bypass failure are limited to few case-series studies (Li et al 2018 ; Gandini et al 2009 ; Davies et al 2017 ), so the need for new studies should be emphasized to better understand long-term outcomes of this option compared to secondary bypass surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published data on secondary femoropopliteal bypass report a primary patency rate of 28-57% and a limb salvage rate of 66-72.4% at 5 years, in patients with CLI (Belkin M et al, 1995;Yang PM et al, 1991;Edwards JE et al, 1990). A more recent retrospective review by Davies (Davies MG et al, 2017) has demonstrated at 3 years an amputation-free survival rate of 56% in the bypass graft group. Besides, when the results are examined, the potential risk of selection bias cannot be ignored.…”
Section: Resultsmentioning
confidence: 95%
“…Gandini (Gandini R et al, 2009) reported a technical success rate of 93.7%, a secondary patency rate of 73.5% at 3 years and a limb salvage rate of 88% at 3 years. Davies (Davies MG et al, 2017) demonstrated in a retrospective review, comparing the outcomes of bypass redoing versus native SFA recanalization in patients with symptomatic femoropopliteal bypass occlusion, that the SFA recanalization group, treated with direct stenting, presented an amputation-free survival rate of 33% ± 9% at 3 years. Furthermore, the data presented in our study are comparable to the results of the primary endovascular treatment of TASC II C and D femoropopliteal lesions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This becomes especially true in the setting of CTOs (TASC C and D lesions), where surgical bypass has historically outperformed endovascular treatment. [9][10][11][12] However, given patient comorbidities and surgical risk, an increasing number of interventionalists approach CTOs with a "percutaneous first" approach despite the lower primary and primary-assisted patency rate. 13 While this is often the preferred treatment option for the patient, a discussion regarding the likelihood and timeframe of reintervention associated with endovascular versus bypass treatment options will benefit both the patient and the interventionalist with appropriate management of expectations.…”
Section: Discussionmentioning
confidence: 99%